(untitled) (Politeja, 2023)
THE TAIWANESE-CHINESE FACTOR IN FRANCE’S STRATEGY AND POLICY TOWARDS THE INDO-PACIFIC The aim of this article is to provide a synthetic overview of France’s involvement into the Indo-Pacific region, in the context of the protection of important national interests related to the possession of overseas territories. This article analyses impact of the French-Chinese bilateral cooperation on relations with Taiwan. The author points out that France has recognized the government of the PRC as the only representative of China since 1964 and does not maintain diplomatic relations with Taiwan, emphasizing that this is a permanent position, initiated by General de Gaulle, and cooperation between Paris and Taipei is developed in accordance with the “one China policy.” The second aspect of the analysis of France’s policy and strategy towards the Indo-Pacific region was embedded in the broader framework of political, economic relations and military alliances with Asian countries as an element of promoting a multipolar order and stopping Chinese expansionism in the Indo-Pacific area and strengthening its own geopolitical position against the background of China’s rivalry with United States.